Analisis Kesalahan Pada Materi Persamaan dan Pertidaksamaan Linear Menggunakan Newmann Error Analysis - Fatimah, Dwi; Nur Baiti Nasution (Absis: Mathematics Education Journal, 2024)
This research aims to analyze students’ errors in solving problems about Linear Equation and Inequalities. The method used in this research is descriptive qualitative. Data collection techniques in this research were tests and interviews. There were 30 students of class VII F SMP Negeri 13 Pekalongan participated in this research. From all of the participants, it was taken 3 students, 1 from each category (high/moderate/low). The 3 students were then to be interviewed about the errors when solving the problems. Types of students’ errors are classified according to Newman’s Error Analysis. The data validity technique in this study was triangulation using the interview method. The results showed that the errors made were type I (reading error) is 0%, type II (comprehension error) is 9%, type III (transformation error) is 15%, type IV error (process skill error) is 34%, and type V (encoding error) is 41%. Based on the interviews, it was found that the error factors were not being able to determine the known elements in the problem, students are not careful in determining what is known in the problem, students cannot change the information in the problem into a mathematical model, students do not know the formula that should be used doing the wrong calculations in solving the problems.